Profile Of Critical Thinking Tendency Students Of The Chemistry And Natural Sciences Education Study Program Institut Studi Islam Sunan Doe - Baiq Anita Febriana; Fathurrahman (Journal of Multidisciplinary Science, 2022)
The tendency to think critically is one of the essential competencies to be mapped from an early age, this student's competence must be analyzed for its development and must constantly be developed because students very much need it to be able to compete in the 21st century later. This study aims to look at the profile of the level of critical thinking tendencies of students of science study programs, namely Chemistry Education and Natural Science at the Institut Studi Islam Sunan Doe. This research was conducted using descriptive and quantitative approaches to see the profile of students' critical thinking tendencies at the Institut Studi Islam Sunan Doe. The research subjects were students of the third semester of the Chemistry and Science Tadris study programs. Data were collected based on the Critical Thinking Tendency test results using a questionnaire adapted from the CCDTI (California Critical Thinking Disposition Inventory). The results of this study indicate that 1) The profile of critical thinking tendencies in chemistry and natural science education students has an average of above 50% in the positive category, which generally means quite good. 2) The indicator of the highest critical thinking tendency in chemistry education students is the Inquisitiveness indicator (curiosity). 3) The indicator of the highest critical thinking tendency for Tadris IPA students is the Truth-seeking indicator.